3
$\begingroup$

Now we want to prove: $$\sum_{n=-\infty}^{\infty}\frac{1}{(n+\alpha)^2}=\frac{\pi^2}{(\sin \pi \alpha)^2}$$ $\alpha$ >0 and not an integer. According to poisson summation formula $$\sum_{n=-\infty}^{\infty}f(x+n)=\sum_{n=-\infty}^{\infty}\hat{f}(n)e^{2\pi inx}.$$ So, if we let $f(x)=\frac{1}{x^2}$, then $$\sum_{n=-\infty}^{\infty}f(x+n)=\sum_{n=-\infty}^{\infty}\frac{1}{(n+x)^2}$$ Therefore, if we can prove that $$\sum_{n=-\infty}^{\infty}\left(\int_{-\infty}^{\infty}\frac{1}{x^2} e^{-2\pi inx}dx e^{2\pi inx}\right)=\frac{\pi^2}{(\sin \pi x)^2}$$ Then it will be done. But I don't know how to prove $$\sum_{n=-\infty}^{\infty}\left(\int_{-\infty}^{\infty}\frac{1}{x^2} e^{-2\pi inx}dx e^{2\pi inx}\right)=\frac{\pi^2}{(\sin \pi x)^2}$$ Who could give me some hints? Thanks!

$\endgroup$
4
$\begingroup$

The proper technique is documented at MSE 112161 and at MSE 3056578.

$\endgroup$
  • $\begingroup$ This one is better done with a rectangular contour aligned with half-integers (real and imaginary). $\endgroup$ – Marko Riedel Dec 30 '13 at 21:15

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.